2019
DOI: 10.35448/jrat.v12i2.6146
|View full text |Cite
|
Sign up to set email alerts
|

Mengintegrasikan Keterampilan Kepemimpinan ke dalam Kurikulum Akuntansi : Persepsi Stakeholders dan Pengujian Model Pembelajaran Kooperatif

Abstract: This study examines the perception of stakeholders (students, lecturers and practitioners) about skills that must be possessed by the students,the feasibility of the accounting curriculum in the development of such skills, and to tests the effectiveness of cooperative learning model in developing leadership skills.To accomplishh this purpose, two studies were conducted. Study 1 investigates the perception of three different parties of stakeholders regarding leadership skills, while the second study tests the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Selama ini, pendekatan pembelajaran Akuntansi telah berkontribusi terhadap kurangnya keterampilan kualitatif dan soft skills mahasiswa (Nsor-Ambala, 2022). Sejalan dengan hal tersebut, kemampuan leadership perlu diintegrasikan ke dalam kurikulum Akuntansi untuk memperluas fokus edukasional di luar pengetahuan teknis (Afriyenti & Misra, 2019).…”
Section: Pendahuluanunclassified
“…Selama ini, pendekatan pembelajaran Akuntansi telah berkontribusi terhadap kurangnya keterampilan kualitatif dan soft skills mahasiswa (Nsor-Ambala, 2022). Sejalan dengan hal tersebut, kemampuan leadership perlu diintegrasikan ke dalam kurikulum Akuntansi untuk memperluas fokus edukasional di luar pengetahuan teknis (Afriyenti & Misra, 2019).…”
Section: Pendahuluanunclassified
“…Cooperative learning results is higher achievement levels for all students, not just those top few who would also be successful in competitive settings (Suarjana & Fathimah, 2021). Naturally enough, cooperative learning helps students develop better interpersonal skills (Afriyenti & Misra, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Suranto (2011) [1] states that the method of interpersonal communication using (indirect) media in certain situations can be an option, for example, in communication. Afriyenti and Misra (2019) [6] found that collaborative learning is useful in building student leadership skills. They suggest that cooperative learning through task groups can build leadership skills, improve communication between students, and increase student satisfaction in collaboration.…”
Section: Introductionmentioning
confidence: 99%